Fixing "bad" capitalism: why CSR and pro-good initiatives may not be enough. Issue 2 (6th September 2019) - Giuliani, Elisa; Nieri, Federica
Abstract : Purpose: The purpose of this paper is to provide a short commentary on the negative consequences of contemporary global capitalism on society. Despite the economic growth experienced across the world over the past century, the so-called grand challenges which include, for instance, rising inequality, global warming, modern slavery and child labor, are becoming endemic phenomena also in high income countries. The authors invite further research to come up with radical ideas to fix "bad" capitalism. Design/methodology/approach: The proliferation of negative business conducts has led international business scholars to propose new ways to address sustainability grand challenges. The articles in this special issue on which the authors were invited to comment, Holmström Lind, Kang, Ljung and Forsgren; Lashitew and van Tulder; Zagelmeyer, are contributing to this agenda. The authors contextualise these articles in the current scholarly discussion on the social role of Multinational Enterprises (MNEs). Findings: Despite all the calls for business to be more responsible and despite the steps taken by MNEs through their Corporate Social Responsibility (CSR) policies, this is not enough to address contemporary grand challenges with any degree of seriousness. Originality/value: The authors invite further research to propose new attempts to fix "bad" capitalism that also involve a rethinking of the way companies reward corporate elites and redistribute their gains.